INTERPRETING GENDER EQUALITY AND WOMEN'S POSITION IN FACING THE RISKS OF THE WORLD OF JOURNALISM (STUDENT PRESS) - Virna Rachma Dani; Ahmad Ridwan; Rizqan Kariema Mustafa (Jurnal Analisa Sosiologi, 2025)
The issue of gender equality in the world of journalism is still a debate, especially related to the position and treatment of female journalists. This study aims to analyze the meaning of gender equality and women's position in facing the risks of the journalistic world, with a focus on female journalists at the Press Institute of the Gema Campus of the State University of Surabaya. The method used is a descriptive qualitative research with a feminist axiology approach, which involves in-depth interviews and observations of female journalists on campus. The results show that although female journalists on this campus have a good understanding of gender equality and are committed to promoting gender inclusion, challenges such as gender stereotypes and discrimination remain significant barriers. Most informants feel that gender equality is important to fight for, but they still face social stigma and the risk of gender-based violence. In addition, Judith Butler's theory of Gender Social Construction shows that public opinion towards women journalists is influenced by social constructions that associate certain traits with gender, thus exacerbating the gap in the world of journalism. This research makes a unique contribution by revealing the dynamics of risks faced by women journalists in the campus environment as a micro-reflection of the broader challenges in the world of journalism. These findings offer a new perspective on the interaction between gender, professional risk, and advocacy in the world of journalism, as well as encourage the formulation of policies that are more responsive to gender equality.